Validity of an on-court lactate threshold test in young basketball players - Castagna, C.; Manzi, V.; Impellizzeri, F.; Chaouachi, A.; Ben Abdelkrim, N.; Ditroilo, M. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to assess the criterion validity of a submaximal field test (Intermittent Shuttle-Running Test [ISRT]) for lactate threshold (LT) detection in young basketball players. Fourteen basketball players (age 15.3 ± 0.6 years, height 182 ± 4.6 cm, and body mass 71.6 ± 6.3 kg) were submitted in random order and on separate occasions, to ISRT (20-m shuttle running for 4 minutes at 9, 10 and 11 km/h) and to a treadmill intermittent progressive test (criterion validity, TM) devised for the assessment of LT (4-minute stages at 8, 10, 12, 14 km/h). Blood-lactate concentrations [La]b were assessed taking earlobe blood samples at rest and immediately after each of the 4-minute running steps considered for ISRT and TM. Lactate threshold was considered as the running speed attained at 1 mmol/L [La]b above resting levels. Results showed that speed at LT during ISRT and TM was significantly related (r = 0.82, p < 0.001). However, speed at LT during the ISRT showed to be significantly lower than the speed at LT during TM (10.1 ± 1.7 vs. 12 ± 2.3 km/h, p < 0.001). During ISRT, players attained 80 ± 4.7, 87 ± 4.4, and 92 ± 3.0% of maximal heart rate (HR) at 9, 10, and 11 km/h, respectively. This study results show that ISRT may be used as a valid field test to assess submaximal aerobic fitness in young team-sport players. Continuous 20-m shuttle running performed at 11 km/h revealed to elicit HR in the range of those reported to induce aerobic-fitness development in trained subjects. In light of study finding, ISRT may be considered in testing batteries for basketball players to complement anaerobic fitness and agility.